1990
DOI: 10.1016/s0006-3495(90)82587-x
|View full text |Cite
|
Sign up to set email alerts
|

On the modulation of a high-enthalpy pretransition in binary mixtures of DMPC and DMPG by polar headgroup interaction

Abstract: Employing high-sensitivity differential scanning calorimetry (DSC), we discovered a pretransition in binary mixtures of dimyristoyl phosphatidylcholine and dimyristoyl phosphatidylglycerol, the main feature of which is its extraordinarily high transition enthalpy of 6.3 Kcal/mol, nearly an order of magnitude higher than those values previously found for such transitions. Using DSC, deuterium nuclear magnetic resonance, and electron microscopy, it is shown that the energetic origin of this type of pretransition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
4
5
0
Order By: Relevance
“…In addition, the order parameters S CD of the DMPC/DMPG mixture are similar to pure DMPC and DMPG. This is in agreement with the near-ideal mixing behavior observed experimentally (40). The bilayers containing DMPS and DMPA have a lower area per lipid (Table 1) and higher order parameters S CD (Fig.…”
Section: Biophysical Propertiessupporting
confidence: 91%
“…In addition, the order parameters S CD of the DMPC/DMPG mixture are similar to pure DMPC and DMPG. This is in agreement with the near-ideal mixing behavior observed experimentally (40). The bilayers containing DMPS and DMPA have a lower area per lipid (Table 1) and higher order parameters S CD (Fig.…”
Section: Biophysical Propertiessupporting
confidence: 91%
“…The onset temperature of the transition to the gel phase is --1 .50C higher for the SSV sample, indicating a destabilization of the liquid crystalline phase of DMPC-d54 due to the interaction with the glass surface. Heating the SSV sample after 3 h incubation at 1OOC now reproduces exactly the course of M, obtained for MLV upon heating (Bayerl et al, 1990a). These results suggest that the detachment of the bilayer from the glass surface occurs during the passage from the liquid crystalline to the gel state.…”
Section: Effects Of the Phase Transitionsupporting
confidence: 72%
“…Finally, the pellets were dried in a vacuum oven for 12 h at 80°C. The quality of surface smoothness and sphericity of the cleaned glass beads was inspected by freeze fracture electron microscopy according to procedures described elsewhere (Bayerl et al, 1988(Bayerl et al, , 1990a). The freeze fracture replicas exhibit smooth, structureless fracture faces indicating an essentially smooth surface of the glass beads.…”
Section: Preparation Of Spherical Supported Vesicle (Ssv) Samplesmentioning
confidence: 99%
“…4. However, in mixtures of DMPC and DMPG, a pretransition has been found that even displays a similar enthalpy to the main transition (Bayerl et al, 1990; cf. Fig.…”
Section: Discussionmentioning
confidence: 99%